Cross-cultural validation of the COVID-19 peritraumatic distress index (CPDI) among Spanish and Peruvian populations - Böttcher, Fabian; Pedraz Petrozzi, Bruno; Lamadé, Eva; Jimenez, Maria Pilar; Rieker, Jennifer; Reales, José Manuel; Arevalo-Flores, Martin; Anculle-Arauco, Víctor; Krüger-Malpartida, Hever; Ballesteros, Soledad (Scientific reports, 2023)
The COVID-19 pandemic has had a significant psychological impact worldwide. The COVID-19 Peritraumatic Distress Index (CPDI) is widely used to assess psychological stress during the COVID-19 pandemic. Although CPDI has been validated in Peru and Spain, no cross-cultural validation studies have been conducted. As an exploratory aim, differences in CPDI factorial scores between the most prevalent medical conditions in the two samples (arterial hypertension, respiratory diseases and anxious-depressive disorders) from a general population of Peru and Spain were investigated. We conducted secondary data analysis with data from Peru and Spain to validate the CPDI in a cross-cultural context. Exploratory factor analysis (EFA) and multigroup confirmatory factor analysis (MGCFA) were performed to evaluate the factor structure and measurement invariance of the CPDI across cultural contexts. Concerning the exploratory analysis, we performed a U-Mann-Whitney test to evaluate differences in the factorial scores in the two samples. This study revealed a two-factor solution (stress and rumination/information) for the CPDI that included 21 of the 24 original items, and consistent with previous studies. The MGCFA demonstrated measurement invariance across cultural contexts (scalar invariance), indicating that the CPDI construct has the same meaning across both groups, regardless of cultural context and language variations of Spanish. Patients with anxious-depressive disorders showed higher CPDI factorial scores for both factors, whereas patients with respiratory diseases were only associated with the stress factor. This study provides evidence for the cross-cultural validity of the CPDI, highlighting its utility as a reliable instrument for assessing psychological stress in the context of COVID-19 across different cultures. These findings have important implications for developing and validating measures to assess psychological distress in different cultural contexts.
Gesehen am 19.06.2024